Efficacy of electro-acupuncture on pregnancy outcomes for women undergoing in vitro fertilization: study protocol for a pilot randomized controlled trial - Zheng, Xiaoyan; Ji, Ran; Li, Chaoliang; Zhu, Hao; Jiang, Ziyi; Zhang, Jingwen; Su, Yang; Yu, Siyi; Yu, Zheng; Lv, Xingyu; Liang, Fanrong; Yang, Jie (Frontiers in Endocrinology, 2024)
Introduction In vitro fertilization (IVF) is a technology that assists couples experiencing infertility to conceive children. However, unsuccessful attempts can lead to significant physical and financial strain. Some individuals opt for electro-acupuncture (EA) during IVF, even though there is limited evidence regarding the efficacy of this practice. Thus, this pilot study aims to explore the effectiveness and safety of EA during IVF on pregnancy outcomes. Methods and analysis This clinical trial is a parallel, randomized, sham-controlled study. It aims to include a total of 118 infertile women who intend to undergo IVF. The participants will be randomly divided into three groups in a 1:1:1 ratio: the EA + IVF group, the placebo electro-acupuncture (pEA) +IVF group, and the IVF control group. All of the patients will be required to use ovarian stimulation drugs, while those in the EA + IVF and pEA + IVF groups will receive acupuncture treatment at three sessions per week (every other day) until trigger day with a minimum five session. The primary outcome of this trial will focus on the clinical pregnancy rate (CPR). CPR is defined as the rate of achieving clinical pregnancy from the first fresh/frozen embryo transfer cycle with an ultrasound-confirmed gestational sac in the uterine cavity. The secondary outcomes will assess embryology data, biochemical pregnancy rate, early miscarriage rate, Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS), Pittsburgh Sleep Quality Index (PSQI), Fertile Quality of Life (FertiQoL), patient retention rate, treatment adherence, and safety outcomes. Ethics and dissemination Ethics approval was obtained from the Ethics Committee of Sichuan Jinxin Xi’nan Women and Children Hospital (number 2021–007). The results will be disseminated through peer-reviewed publications. The participants gave informed consent to participate in the study before taking part in it. Clinical trial registration https://www.chictr.org.cn, identifier ChiCTR2300074455.